Shape-based separation of drug-treated Escherichia coli using viscoelastic microfluidics. Issue 15 (1st June 2022) - Zhang, Tianlong; Liu, Hangrui; Okano, Kazunori; Tang, Tao; Inoue, Kazuki; Yamazaki, Yoichi; Kamikubo, Hironari; Cain, Amy K.; Tanaka, Yo; Inglis, David W.; Hosokawa, Yoichiroh; Yaxiaer, Yalikun; et al.
Abstract : A viscoelastic microfluidic device for shape-based separation of drug-treated Escherichia coli . Abstract : Here, we achieve shape-based separation of drug-treated Escherichia coli ( E. coli ) by viscoelastic microfluidics. Since shape is critical for modulating biological functions of E. coli, the ability to prepare homogeneous E. coli populations adopting uniform shape or sort bacterial sub-population based on their shape has significant implications for a broad range of biological, biomedical and environmental applications. A proportion of E. coli treated with 1 μg mL −1 of the antibiotic mecillinam were found to exhibit changes in shape from rod to sphere, and the heterogeneous E. coli populations after drug treatment with various aspect ratios (ARs) ranging from 1.0 to 5.5 were used for experiment. We demonstrate that E. coli with a lower AR, i.e., spherical E. coli (AR ≤ 1.5), are directed toward the middle outlet, while rod-shaped E. coli with a higher AR (AR > 1.5) are driven to the side outlets. Further, we demonstrate that the separation performance of the viscoelastic microfluidic device is influenced by two main factors: sheath-to-sample flow rate ratio and the concentration of poly-ethylene-oxide (PEO). To the best of our knowledge, this is the first report on shape-based separation of a single species of cells smaller than 4 μm by microfluidics.